Correlation between vitamin D and poor sleep status in restless legs syndrome - Geng, Chaofan; Yang, Zhenzhen; Kong, Xiumei; Xu, Pengfei; Zhang, Hongju (Frontiers in Endocrinology, 2022)
Background: Restless Legs Syndrome (RLS) is closely related to sleep disorder. Vitamin D plays an important role in cell proliferation, differentiation, sleep regulation. The aim of this study was to measure whether vitamin D has predictive value for sleep disorders in RLS. Methods: The serum levels of 25-hydroxyvitamin D [25(OH)D] were retrospectively analyzed in 95 RLS patients. The sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI). According to the PSQI score, subjects were divided into sleep disorders (SD) group and non-sleep disorders (NSD) group. Using correlation and regression analysis to explore underlying etiologies affect sleep disorder in RLS patients. Results: Patients in SD group had significantly lower vitamin D levels in comparison to NSD group. In patients with RLS, a significant negative correlation between serum vitamin D levels and PSQI scores remained after adjusting for confounding factors. In addition, regression analysis showed that vitamin D could act as a predictor for sleep disorders in RLS patients (odds ratio [OR] = 0.008, p = 0.004). According to the receiver operating characteristic (ROC) analysis, the area under the curve (AUC), cut-off value, sensitivity, and specificity of serum vitamin D was 0.967 (95% CI 0.935–0.998), 16.84 ng/ml, 87.5%, and 93.7%. Conclusion: Our study confirmed the relationship between vitamin D and sleep disorders in RLS. However, the causal relationship between vitamin D deficiency and RLS is currently inconclusive. Prospective cohort studies are needed to confirm the effect of vitamin D supplementation as the therapeutic strategies for sleep disorders in RLS patients in future work.